PERAN SUFISME DALAM MENGATASI PAHAM ISLAM RADIKAL DI INDONESIA - Abshor, Ulil (Al-Banjari : Jurnal Ilmiah Ilmu-Ilmu Keislaman, 2019)
Radical Islamic Movement or Islamic Radicalism is a movement that has a mindset of textualist ideology, takfiri and truth claim. Basically, the context in which a religious understanding that is claimed to be the final truth, certainly contains an exclusive and offensive element so that some views, flow, and any schools outside is deemed as deviant, because it is far from authoritative sources originating from the Qur'an and the Sunna. This phenomenon does not reflect the peace of Islam as taught by the Prophet as rahmatan lil ?Alamiin (mercy for all nature). This article explores further the importance of the role of Sufism related to the spiritual teachings in it which are the basic foundation in realizing Islam that is peaceful, tolerant, respectful, respectful among fellow human beings especially among other religious people. Islamic teachings extracted in Sufism contain solutive elements in fulfilling the true spirit of Islamic migration (hijra). The Sufism values contain restraints on an "engine of desire" which is now sweeping through modern society. In these conditions, in the face of challenges for the reduction of the spirit of radicalism, consistency (tawakkal) is needed, namely the form of tireless cleansing of the soul.Gerakan Islam Radikal atau Radikalisme Islam merupakan gerakan yang memiliki pola pikir ideologi tekstualis, takfiri dan truth claim. Pada dasarnya, konteks di mana sebuah pemahaman keagamaan yang diklaim sebagai kebenaran final, tentu mengandung unsur eksklusif dan ofensif sehingga paham, aliran, madzhab apapun diluar dirinya dianggap menyimpang, karena jauh dari sumber otoritatif yang berasal dari al-Qur?an dan al-Sunnah. Fenomena tersebut tidak mencerminkan kedamaian Islam sebagaimana yang diajarkan oleh Rasulullah Saw. sebagai rahmatan lil ?Alamiin (rahmat bagi seluruh alam). Artikel ini mengeksplor lebih jauh tentang pentingnya peran nilai-nilai sufisme terkait ajaran-ajaran spiritual di dalamnya yang menjadi pondasi pokok dalam merealisasikan Islam yang damai, toleran, saling menghargai, menghormati antar sesama umat manusia terlebih antar umat agama lain. Ajaran Islam yang terekstrak dalam sufisme mengandung unsur solutif dalam memenuhi semangat hijrah keislaman yang sesungguhnya. Nilai-nilai sufisme yang dimaksud mengandung pengekangan terhadap sebuah ?mesin hasrat? yang kini melanda masyarakat modern. Di dalam kondisi seperti ini, dalam menghadapi tantangan demi berkurangnya spirit radikalisme, diperlukan konsistensi (tawakkal) yaitu bentuk penyucian jiwa yang tak kenal lelah.